2021
DOI: 10.1007/s00404-021-06002-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the uterocervical angle for the prediction of preterm birth in symptomatic women

Abstract: Purpose To examine if the uterocervical angle (UCA) can be used to predict preterm delivery in women with painful and regular uterine contractions and a cervical length of 25 mm or less. Methods Retrospective study at the perinatal unit of the University Hospital of Tuebingen, Germany. Women with singleton gestation and preterm contractions between 24 + 0 and 33 + 6 weeks’ gestation were included. For the UCA measurement, a line is placed from the internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(44 reference statements)
0
12
0
1
Order By: Relevance
“…A total of 192 articles were retrieved from PubMed, Embase, the Cochrane database, WHO ICTRP, Web of Science, and ClinicalTrials.gov and through manual search. After excluding duplicates and ineligible studies, 22 studies were included in the qualitative analysis, including 11 prospective cohort studies, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 7 retrospective cohort studies, 24 , 25 , 26 , 27 , 28 , 29 , 30 and 4 case-control studies. 31 , 32 , 33 , 34 Of note, 1 study was not included in the meta-analysis because of incomplete data.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 192 articles were retrieved from PubMed, Embase, the Cochrane database, WHO ICTRP, Web of Science, and ClinicalTrials.gov and through manual search. After excluding duplicates and ineligible studies, 22 studies were included in the qualitative analysis, including 11 prospective cohort studies, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 7 retrospective cohort studies, 24 , 25 , 26 , 27 , 28 , 29 , 30 and 4 case-control studies. 31 , 32 , 33 , 34 Of note, 1 study was not included in the meta-analysis because of incomplete data.…”
Section: Resultsmentioning
confidence: 99%
“…Regrettably, the data did not support any of these markers in the same way that our results did. 19 There is some confirmation, that a wider UCA is allied to PTB before 34 weeks of gestation. Daskalakis et al 20 assessed the existing body of literature about 3,000 women.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the uterocervical angle, an acute angle reinforces the closure of the endocervical canal, while a more obtuse angle may facilitate the opening of the cervix (23); this could be the reason why Luechathananon et al, obtained a higher cutoff value compared to our study (110.97 ° vs 89.81 ° or 81) (22). In contrast to our study, results obtained by Wagner et al, showed that the uterocervical angle is not a useful measure for the prediction of preterm birth, the included patients in this study accounted for that difference as they included patients with regular uterine contractions and cervical length less than 25mm which indicated a very high risk for preterm delivery; an obtuse uterocervical angle was predominant in the three study groups that were delivery within 2 days, 3-7 days and after 7 days with corresponding median UCA angle of 108.5, 108°, and 107.3° (24). The value of these ndings is that when it comes to patients with already established uterine contractions and cervical changes, the value of the uterocervical angle in predicting preterm delivery is questioned.…”
Section: Discussionmentioning
confidence: 99%